Disclosure of risks in the negotiation phase of technology transfer contracts - Acer Isam Dawood (الرافدین للحقوق, 2018)
The disclosure of the dangers in the negotiations stage is one of the main obligations of the technology supplier, since the negotiations are a pre-conclusion stage of the technology transfer contract and it is important and the undeniable role in the formation of the contract and then its implementation. The principle of good faith can be considered as the legal basis for the obligation to disclose risks at the negotiation stage, since the basis for contracts in the scope of their implementation is the principle of good faith. The jurisprudence tends to distinguish between two types of ways of disclosing dangers and children. To identify those who are retarded. Violation of the disclosure obligation would result in an appropriate legal sanction, which would require legislative intervention specifying the terms, limits, image, and consequences of the breach.